Deciding on child maltreatment: A literature review on methods that improve decision-making. (November 2015) - Bartelink, Cora; van Yperen, Tom A.; ten Berge, Ingrid J.
Abstract: Assessment and decision-making in child maltreatment cases is difficult. Practitioners face many uncertainties and obstacles during their assessment and decision-making process. Research exhibits shortcomings in this decision-making process. The purpose of this literature review is to identify and discuss methods to overcome these shortcomings. We conducted a systematic review of the published literature on decision-making using PsychINFO and MEDLINE from 2000 through May 2014. We included reviews and quantitative research studies that investigated methods aimed at improving professional decision-making on child abuse and neglect in child welfare and child protection. Although many researchers have published articles on decision-making including ideas and theories to improve professional decision-making, empirical research on these improvements is scarce. Available studies have shown promising results. Structured decision-making has created a greater child-centred and holistic approach that takes the child's family and environment into account, which has made practitioners work more systematically and improved the analysis of complex situations. However, this approach has not improved inter-rater agreement on decisions made. Shared decision-making may improve the participation of parents and children and the quality of decisions by taking client treatment preferences into account in addition to scientific evidence and clinical experience. A number of interesting developments appear in recent research literature; however, child welfare and child protection must find additional inspiration from other areas, e.g., mental health services, because research on decision-making processes in child welfare and child protection is still rare.